1996
DOI: 10.1128/aac.40.8.1801
|View full text |Cite
|
Sign up to set email alerts
|

Group of peptides that act synergistically with hydrophobic antibiotics against gram-negative enteric bacteria

Abstract: A synthetic peptide, KFFKFFKFFK [corrected], consisting of cationic lysine residues and hydrophobic phenylalanine residues was found to sensitize gram-negative bacteria to hydrophobic and amphipathic antibiotics. At a concentration of 3 micrograms/ml, it decreased the MIC of rifampin for smooth, encapsulated Escherichia coli by a factor of 300. Other susceptible bacterial species included Enterobacter cloacae, Klebsiella pneumoniae, and Salmonella typhimurium, but Pseudomonas aeruginosa was resistant. Similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(105 citation statements)
references
References 20 publications
2
103
0
Order By: Relevance
“…In fact, the cationic peptides allow maximal entry of several substrates into the cell. On the other hand, a general permeability-increasing effect on the cytoplasmic membrane by the peptides is not likely to be the main reason for this positive interaction and it is possible that it may be the result of a combined effect of increased access to the intracellular target for antibiotics and secondary effects of the peptide itself [13,[26][27][28]. This hypothesis could include increased uptake and accessibility to the target, combined with drugs acting on a common pathway.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, the cationic peptides allow maximal entry of several substrates into the cell. On the other hand, a general permeability-increasing effect on the cytoplasmic membrane by the peptides is not likely to be the main reason for this positive interaction and it is possible that it may be the result of a combined effect of increased access to the intracellular target for antibiotics and secondary effects of the peptide itself [13,[26][27][28]. This hypothesis could include increased uptake and accessibility to the target, combined with drugs acting on a common pathway.…”
Section: Discussionmentioning
confidence: 84%
“…The KFFKFFKFFK peptide used in this study was originally reported as a potent permeabilizer of E. coli cells [17]. The mechanism of uptake for such peptides and their capacity to deliver cargo molecules into cells are controversial, and there is evidence for both energy-dependent and energy-independent mechanisms [18].…”
Section: Anti-gfp Effects Of Various Attached Peptides As Carriers Fomentioning
confidence: 99%
“…4a, nisin Z at 5 nM efficiently caused permeabilisation of the S. aureus cytoplasmic membrane, whereas pre-treatment of S. aureus with 500 M vancomycin prior to nisin Z incubation completely inhibited the cytoplasmic membrane permeabilisation. To compare nisin Z with other antimicrobial peptides, a cationic antimicrobial peptide SAEP-4 with vancomycin-independent activity [17,24] was used as a control. Similarly, the SAEP-4 was incubated with S. aureus in the presence or absence of vancomycin.…”
Section: Inhibitory Effect Of Nacl and Vancomycin On Cytoplasmic Membmentioning
confidence: 99%
“…Concentrations of nisin Z were determined based on HPLC peak area. As a control, a cationic antimicrobial peptide (SAEP-4: KFFKFFKFF) [16,17] was synthesised as described previously [18].…”
Section: Reagentsmentioning
confidence: 99%